Internet Transparentnost u Finansijskom Sektoru Bosne i Hercegovine/ Internet Transparency in Financial Sector in Bosnia and Herzegovina - Zlatković Matea (ECONOMICS, 2015)
Raising the quality of corporate governance has a direct positive impact on company’s market value, allowing the use of variety of forms of financing: national and international, public and private, which strengthen their long-term development. The purpose of this paper is to explore the Internet transparency in banks and insurance companies in Bosnia and Herzegovina and detect the differences between the banking and insurance sectors in terms of transparency in certain areas of corporate governance. The necessary data for the study were obtained by reviewing corporate websites. The results of discrimination analysis show that there is a difference in the internet transparency between banking and insurance sectors in Bosnia and Herzegovina.